ANTIFUNGAL ACTIVITY OF MANGIFERA INDICA LEAF EXTRACT ON FUNGI ISOLATED FROM BREAD VENDED WITHIN BAKORI, NIGERIA - BASHIR KUTAWA, ABDULAZIZ; BAKORI, SALMAN SADA; MUSA, HABU (Innovare Journal of Agricultural Sciences, 2021)
Objective: The present study was carried out to determine the antifungal activity of Mangifera indica leaves extract on fungi isolated from bread vended within Bakori. Methods: The powdered form of M. indica leaves was used to prepare the extract using ethanol, the leaves were air dried at room temperature for 10 days. Results: The chemical test was carried out to identify the secondary metabolites, some of the metabolites that were present include alkaloids, saponins, flavonoids, steroids, and tannins. Both fungal isolates were identified on the basis of morphological characteristics as Aspergillus niger, Aspergillus flavus, and Mucor spp. The antifungal activity of M. indica leaves extract was determined using agar well diffusion method on Aspergillus and Mucor spp. The results showed that the extract was found to inhibit A. niger at 100 mg/ml, 50 mg/ml, and 25 mg/ml with 13.9 mm, 11.5 mm, and 8.0 mm, respectively, and A. flavus at 100 mg/ml, 50 mg/ml, and 25 mg/ml with 13.6 mm, 11.2 mm, and 8.1 mm, respectively, while Mucor spp. was found to be resistant at 25 mg/ml while 100 mg/ml and 50 mg/ml showed an activity. Minimum inhibitory concentration result showed a promising activity against Aspergillus spp. at 25 mg/ml while Mucor spp. at 50 mg/ml. Conclusion: Therefore, M. indica leaf extracts can be used in the treatment of diseases or illness caused by Aspergillus and Mucor spp.